PENGARUH KONTRIBUSI OBJEK WISATA PANTAI GANDORIAH PARIAMAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PARIAMAN - Rosa, Yenni Del (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
This study aims to determine the effect of the contribution of Gandoriah Pariaman Beach tourism object consisting of hotel tax, restaurant tax, tourist attraction, ticket sales and motor vehicle parking to Pariaman area in 2013 - 2017 partially and simultaneously. The data analysis used multiple linear regression of Ordinary Least Square with SPSS program version 21. Before the data is processed it turns out all free and bound variable data meet the classical assumptions of multicolinearity testing, autocorrelation and heteroscedasticity. The result of multiple linear regression equation Y = 3.125 + 0.021X1 + 0.087X2 + 0.243X3 + 0.579X4 + 0.375X5 + e. After the hypothesis testing was found all the contribution of Gandoriah Pariman Beach tourism object has a significant positive effect on the original income of Pariaman district region partially (t test) and simultaneously (F test) at 5% significance level. This is also shown by the value of the correlation coefficient (R = 0.679) and the value of Adjusted R Square = 0.579Keywords: hotel tax contribution, restaurant tax, tourist attraction, ticket sales, motorvehicle parking and Local Own Revenue